2005
DOI: 10.1016/j.susc.2005.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermal stability of ceria films supported on YSZ(100) and α-Al2O3(0001)

Abstract: The morphology and reducibility of vapor-deposited ceria films supported on yttria-stabilized zirconia (100) (YSZ(100)) and α-Al 2 O 3 (0001) single crystals were studied using X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM). The results of this study show that the gas environment has a significant effect on the structure of the ceria films on both substrates. CeO 2 films on α-Al 2 O 3 (0001) were found to be stable in a reducing environment at temperatures up to 1000K, but underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The second surprise is the large change in ceria morphology that occurs upon treatment of ceria at a temperature of only 973 K. That macroscopic movement of ceria in contact with YSZ can occur following oxidation and reduction has already been demonstrated with ceria films on YSZ single crystals [28,29], but this movement has not previously been reported to affect fuel-cell properties. Furthermore, the previous work with ceria films on YSZ found that reduction caused ceria to "spread" over the YSZ surface, the opposite of what appears to be occurring to ceria upon methanol exposure in the fuel cell.…”
Section: Discussionmentioning
confidence: 99%
“…The second surprise is the large change in ceria morphology that occurs upon treatment of ceria at a temperature of only 973 K. That macroscopic movement of ceria in contact with YSZ can occur following oxidation and reduction has already been demonstrated with ceria films on YSZ single crystals [28,29], but this movement has not previously been reported to affect fuel-cell properties. Furthermore, the previous work with ceria films on YSZ found that reduction caused ceria to "spread" over the YSZ surface, the opposite of what appears to be occurring to ceria upon methanol exposure in the fuel cell.…”
Section: Discussionmentioning
confidence: 99%
“…The results further imply that our films are essentially bulk-like in nature, with low strain energy, consistent with the thickness independent lattice constant, and minimal influence of low-angle tilt boundaries present in the growth direction, consistent with the narrow FWHM measured in the rocking curve diffraction experiment. In contrast, in very thin films, 10 nm or less, 37 and in nanostructured bulk materials 38 , where K 00 directly yields the standard Gibb's free energy of cerium reduction. …”
Section: à2mentioning
confidence: 99%
“…The LA support was chosen because of its high surface area and excellent thermal stability under redox conditions. Also, we anticipated that interactions between ceria and LA would have a negligible effect on the reducibility of ceria, in contrast to the strong promotion of ceria reduction observed with ceria on zirconia [35,41]. Unlike pure ceria, the ceria/LA samples were found to be quite stable to redox cycling.…”
Section: High-surface-area Ceria and Ceria/lamentioning
confidence: 99%
“…To minimize formation of ceria aluminates [35] and maintain surface area following hightemperature treatment, the alumina was doped with 11.5-wt% La 2 O 3 . The effect of rare-earth dopants was also studied on bulk samples doped with Y +3 and Sm +3 .…”
Section: Introductionmentioning
confidence: 99%